Systematic review of guidelines for managing physical health during treatment for substance use disorders: Implications for the alcohol and other drug workforce. (28th June 2022) - Osborne, Briony; Larance, Briony; Ivers, Rowena; Deane, Frank P.; Robinson, Laura D.; Kelly, Peter J.
Abstract: Issues: Substance use disorders are associated with significant physical health comorbidities, necessitating an integrated treatment response. However, service fragmentation can preclude the management of physical health problems during addiction treatment. The aim of this systematic review was to synthesise the recommendations made by clinical practice guidelines for addressing the physical health of people attending alcohol and other drug (AOD) treatment. Approach: An iterative search strategy of grey literature sources was conducted from September 2020 to February 2021 to identify clinical practice guidelines. Content pertaining to physical health care during AOD treatment was extracted. Quality of guidelines were appraised using the Appraisal of Guidelines Research and Evaluation II (AGREE‐II) tool. Findings: Thirty‐three guidelines were included for review. Fourteen guidelines were considered high quality based on AGREE‐II scores. Neurological conditions (90.9%) and hepatitis (81.8%) were the most frequent health problems addressed. Most guidelines recommended establishing referral pathways to address physical health comorbidities (90.9%). Guidance on facilitating these referral pathways was less common (42.4%). Guidelines were inconsistent in their recommendations related to oral health, tobacco use, physical activity, nutrition and the use of standardised assessment tools. Implications and Conclusions: Greater consistency and specificity in the recommendations made for integrating physical health care within addiction treatment is needed. Ensuring that recommendations are applicable to the AOD workforce and to treatment services limited by funding and resource constraints should enhance implementation. Future guideline development groups should consider increased consultation with the AOD workforce and inclusion of clinical tools and decision aids to facilitate referral pathways.